Development of POLELA Educational Video on Balloon and Lantern Sleeve Patterns for Fashion Design Students - Yunita Asfia; Evania Yafie; Siti Ubaidah; Thiessa Krisnanda; Yusrin Nasrillah (Jurnal Media dan Teknologi Pendidikan, 2025)
Many students face difficulties in mastering the steps of creating balloon and lantern sleeve patterns, which affects their achievement in the Pattern Making course. Conventional teaching methods, such as lectures and board demonstrations, have proven less effective in accommodating diverse learning styles. This study aimed to develop and evaluate the effectiveness of the educational video POLELA (Balloon and Lantern Sleeve Patterns) in enhancing students’ understanding and independent learning in Grade X Fashion Design and Production programs. This research employed a Research and Development (R&D) approach using the ADDIE model, covering the stages of Analysis, Design, Development, Implementation, and Evaluation. The subjects included content experts, media experts, and 30 students as a limited trial sample. Data were collected through a four point Likert scale questionnaire and analyzed descriptively. The results indicated content validation with an average score of 3.43, media validation 3.63, and 95.33% positive student responses, showing that the POLELA video is highly feasible, practical, and effective. The findings suggest that integrating audiovisual elements in Pattern Making instruction can improve conceptual understanding, engagement, and students’ independent learning. The implication is that educational videos like POLELA can serve as a flexible and innovative teaching strategy and are recommended for broader implementation in vocational education to support the development of students’ practical skills.